Tension pneumothorax due to perforated colon - Abdullah, Muhammad (BMJ Case Rep, 2016)
A very rare case of traumatic diaphragmatic hernia is reported in a 65-year-old woman who presented 46 years after her initial thoracoabdominal injury with tension faecopneumothorax caused by a perforated colon in the chest cavity. She presented in a critical condition with severe respiratory distress, sepsis and acute kidney injury. She had a long-standing history of bronchial asthma with respiratory complications and had experienced progressive shortness of breath for the past year. A recent CT scan had excluded the presence of a diaphragmatic hernia but showed a significantly raised left hemidiaphragm. On admission, chest X-rays showed a significantly raised left hemidiaphragm and mediastinal shift, but the possibility of a diaphragmatic hernia with strangulated bowel in the chest was not suspected until the patient was reviewed by the surgical and intensive care unit consultants the next morning and a repeat CT performed. She had a successful outcome after her emergency operation.